Coactions of bitterbrush, ponderosa pine, and herbaceous vegetation - Giunta, Bruce Conrad, author; Mogren, Edwin W., advisor; Van Dyne, George M., committee member (Colorado State University. Libraries, 1968)
During 1966 and 1967, 100 bitterbrush (Purshia tridentata) plants were collected on each of six study areas located approximately 30 miles west of Fort Collins, Colorado. Study areas were selected to provide varying levels of abundance of bitterbrush, ponderosa pine (Pinus ponderosa), and herbaceous vegetation. The object was to relate bitterbrush age structures, growth, and vigor to plant c o actions. Bitterbrush plants were aged by ring count. Living and dead portions of the crown were weighed separately. Various measurements were made at each bitterbrush plant and on the plot where it occurred. These were intended to relate the shrub component to herbaceous cover and indices of ponderosa pine abundance. Grasses were the most important herbaceous component on all study areas. Ponderosa pine varied from 0 ft /acre on study area three to 102 ft /acre of basal area on area six. Sexual regeneration of bitterbrush appears rare on all study areas, but especially where a pine canopy is absent. Asexual reproduction by layering was common. A chi-square test of homogeneity comparing age structures between study areas yielded significant results. However, no relationship between age structure and pine or herbaceous abundance was evident. Three of the study areas appear to have declining bitterbrush stands. Investigations of growth rate revealed that bitterbrush may experience a peak growth rate that is at least partially controlled by age. Multiple regression analysis indicated that growth rate is inversely related to ponderosa pine basal area. Bitterbrush plants of a given age are almost always larger in open stands than under a canopy. No relationship with herbaceous cover could be detected. Attempts to quantify bitterbrush vigor were a failure, because of extreme variation in percent dead crown material between plants. Crown die back could not be related to pine or herbaceous abundance. Current annual growth production of bitterbrush seems inversely related to herbaceous cover and the percent of dead crown material present.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Purshia tridentata; Ponderosa pine